Georesistivity index of composite geostrata at different conditions / Noorasyikin Mohammad Noh - Mohammad Noh, Noorasyikin (2011)
A geotechnical engineering exploration begins with a site investigation of the subsurface to determine the ground stabilization for the proposed construction. There are two types of techniques that have been used widely in site investigation; destructive techniques for examples testing material from samples extracted through the drilling method and non-destructive techniques for example the resistivity method. The conventional destructive techniques have the disadvantages of sampling disturbance that would affect the data accuracy because of disturbance and contaminant. For non-destructive technique, it is known to be optimum, insitu condition and higher accuracy of data. In this study, a non-destructive innovative laboratory technique of georesistivity technique has been developed for geocharacterization of laboratory scale material and georesistivity tank modeling with stratified materials. The main objectives of this study are to determine the physical properties and georesistivity index of geo materials, to determine the 2D georesistivity profiling of stratified soil and hard layer, and to correlate the georesistivity index with physical properties of materials. It is found that the resistivity of geological samples depends on several factors. These include the amount of water present in the pores and its porosity. The dominant factors that typically determine a sample's resistivity are the amount of the fluid as conductor where dry material will be more resistive than wet material. From the pilot study, it is found that the presence of clay minerals, such as montmorillonite, results in low resistivity and the materials contains water soluble minerals, such as salt, also result in a low resistivity from the addition of water.